Genome Triplication Leads to Transcriptional Divergence of FLOWERING LOCUS C Genes During Vernalization in the Genus Brassica - Akter, Ayasha; Itabashi, Etsuko; Kakizaki, Tomohiro; Okazaki, Keiichi; Dennis, Elizabeth S.; Fujimoto, Ryo (Frontiers in Plant Science, 2021)
The genus Brassica includes oil crops, vegetables, condiments, fodder crops, and ornamental plants. Brassica species underwent a whole genome triplication event after speciation between ancestral species of Brassica and closely related genera including Arabidopsis thaliana. Diploid species such as Brassica rapa and Brassica oleracea have three copies of genes orthologous to each A. thaliana gene, though deletion in one or two of the three homologs has occurred in some genes. The floral transition is one of the crucial events in a plant’s life history and time of flowering is an important agricultural trait. There is variation in flowering time within species of the genus Brassica, and this variation is largely dependent on a difference in vernalization requirements. In Brassica, like in A. thaliana, the key gene of vernalization is FLOWERING LOCUS C (FLC). The vernalization response including the repression of FLC expression by cold treatment and the enrichment of the repressive histone modification tri-methylated histone H3 lysine 27 (H3K27me3) at the FLC locus is similar to A. thaliana. B. rapa and B. oleracea each have four paralogs of FLC, and the allotetraploid species, Brassica napus, has nine paralogs. The increased number of paralogs makes the role of FLC in vernalization more complicated; in a single plant, paralogs vary in the expression level of FLC before and after vernalization. There is also variation of FLC expression levels between accessions. In this review, we focus on the regulatory circuits of the vernalization response of FLC expression in the genus Brassica.